Developing a Problem-Based Learning E-Module to Enhance Students Understanding of Elements, Compounds and Mixtures in Chemistry - Dalilah, Dalilah; Erlina*, Erlina; Mayasari, Eni; Salam, Supriatno (Universitas Syiah Kuala, 2025)
This study evaluates the viability of a problem-based learning (PBL) e-module on elements, compounds, and mixtures through validation by experts and feedback from both teachers and students. This study adopted a research and development (RD) methodology guided by the ADDIE framework. The participants consisted of teachers and students from SMPN 10 Pontianak. The data were gathered using an indirect communication method, specifically through feasibility assessment sheets and questionnaires filled out by both teachers and students. The results indicated that the e-module was considered highly suitable for use. The validity coefficient were 1.00 from graphic design experts (categorized as very good), 0.83 from linguists (very good), and 1.00 from subject matter experts (very good). The average coefficient from experts validation was 0.94, which fall into the very good category. In addition, teacher and student responses also indicated very good results: for the media aspect, each response rates were 92% and 85%; for the content aspect, 85% and 83%; and for usefulness, 86% and 85%. These results suggest that the PBL-based teaching e-module is suitable and ready to be used in learning activities